First report of Mycobacteroides abscessus subsp. massiliense and Erysipelothrix rhusiopathiae as causative agents of pneumonia and hepatitis in a boa (Boa constrictor) - Oca, Juan Pablo Velasco-Montes de; Romero-Romero, Laura P.; Hernández-Castro, Rigoberto; Martínez-Chavarría, Luary C (Brazilian Journal of Veterinary Pathology, 2023)
An adult boa with acute epistaxis, without other clinical signs, was found dead in its terrarium. Macroscopic examination of the specimen revealed multiple yellow foci in the lung and liver. Microscopic findings included severe and multifocal granulomas as well as vasculitis, hemorrhages and thrombosis in liver and lungs, with the presence of intralesional Gram positive and acid-fast bacilli. PCR end point analysis and sequencing using total DNA extracted from formalin-fixed paraffin-embedded samples of liver and lungs identified Mycobacteroides abscessus subsp massiliense and Erysipelothrix rhusiopathiae. Mycobacteria are organisms that can affect a wide range of animals, including reptiles. In snakes, reports are rare and mycobacterial species are highly variable. Erysipelothrix rhusiopathiae is a pathogenic bacillus related to multiple organ disorders, which until now has not been reported in boas. This report describes the first case report of Mycobacteroides abscessus subsp. massiliense and Erysipelothrix rhusiopathiae detection in a boa.